Perinatal Mortality and Associated Factors Among Antenatal Care Attended Pregnant Mothers at Public Hospitals in Gamo Zone, Southern Ethiopia - Dessu, Samuel; Dawit, Zinabu (Frontiers in Pediatrics, 2020)
Introduction: Perinatal mortality is the death of a baby between 28 weeks of gestation onwards and before the first seven days of life. According to WHO, Ethiopia is one of the most commonly noticed countries in the world in considering perinatal mortality rate. The overall perinatal mortality rate in Ethiopia was around sixty-six to one hundred twenty four per 1000 births. Objective: To determine the magnitude of perinatal mortality and associated factors among mothers attending antenatal care at public hospitals in Gamo Gofa Zone, Southern Ethiopia. Methods: Facility-based cross-sectional study was conducted at Arba Minch General hospital and Chencha district hospitals from 1st Jan, 2018 to 31st Dec; 2018G.C using simple random sampling method for the predetermined 1820 records. Both bivariate and multivariable logistic regression analysis was conducted. Variables that had p-value <0.25 in bivariate analysis were considered as a candidate variable for multivariable analysis and variables which had P-value <0.05 in multivariable analysis were declared as statically significant. Results: The magnitude of perinatal mortality was 12.6%(95%CI: 11.80, 13.40) and grand multiparity(AOR: 7.40; 95% CI: 2.77, 20.26), having one antenatal visit(AOR: 4.40; 95% CI: 1.64, 11.91), spontaneous vaginal delivery(AOR: 0.36; 95% CI: 0.16, 0.82), being preterm(AOR: 6.78; 95% CI: 2.41, 19.09), birth weight <2500gram(AOR: 3.10; 95% CI: 1.48, 6.46), maternal ever hemoglobin level during pregnancy <10gm/dl during pregnancy(AOR: 4.04; 95% CI: 1.91, 8.57) and prepartum onset of pregnancy induced hypertension(AOR: 4.01; 95% CI: 0.01, 0.08) were statistically significant in multivariable logistic regression model. Conclusion: There was a high magnitude of perinatal mortality and high parity, mode of delivery, low gestational age, low birth weight, low maternal hemoglobin level and prepartum onset of pregnancy-induced hypertension were factors which are independent factors associated with perinatal mortality. Therefore; the community should be educated to reduce the number of births and modes of delivery. In addition, health care professionals should emphasize the care provided for the newborns having low birth weight.